1999
DOI: 10.1021/es990334s
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Reduction of Chromate and PCE by Pelletized Surfactant-Modified Zeolite/Zerovalent Iron

Abstract: The current research focuses on enhanced removal of chromate and perchloroethylene from contaminated water by a combination of a reduction material (represented by zerovalent iron, ZVI) and a sorption material (represented by surfactant-modified zeolite, SMZ). Natural zeolite and ZVI were homogenized and pelletized to maintain favorable hydraulic properties while minimizing material segregation due to bulk density differences. The zeolite/ZVI pellets were modified with the cationic surfactant hexadecyltrimethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(61 citation statements)
references
References 22 publications
2
53
0
3
Order By: Relevance
“…In the field, Fenton's reagent (Fe 2+ /H 2 O 2 ) has been used in recent years to remove or transform a variety of pollutants, including TNT, found in groundwater or wastewater treatment streams Stenstrom 2002, Oh et al 2003). Li et al (1999) found that Fenton's reagent was more effective at pH 6 than pH 3 due to the precipitation of Fe 3+ at pH >5. Because marine ecosystems have a pH near 8, Fenton chemistry may mediate some component of TNT degradation through active photochemical redox cycling of iron (Miller et al 1995), an important component of which is H 2 O 2 generation.…”
Section: Abiotic --Photolysismentioning
confidence: 97%
“…In the field, Fenton's reagent (Fe 2+ /H 2 O 2 ) has been used in recent years to remove or transform a variety of pollutants, including TNT, found in groundwater or wastewater treatment streams Stenstrom 2002, Oh et al 2003). Li et al (1999) found that Fenton's reagent was more effective at pH 6 than pH 3 due to the precipitation of Fe 3+ at pH >5. Because marine ecosystems have a pH near 8, Fenton chemistry may mediate some component of TNT degradation through active photochemical redox cycling of iron (Miller et al 1995), an important component of which is H 2 O 2 generation.…”
Section: Abiotic --Photolysismentioning
confidence: 97%
“…Enhanced removal of Cr(VI) from contaminated water was also achieved using a combination of ZVI and sorbents such as zeolite/ZVI pellets, prepared by mixing ZVI and zeolite at a mass ratio 73:20 on a rotating dish with a binder (7% of the total weight, made of 1:1 by weight of sodium silicate and sodium aluminate in liquid form), washed with CaCl 2 solution and dried in an oven at 177°C (Li et al 1999. Another laboratory method was suggested by Dos Santos Coelho et al (2008) who used for Cr(VI) reduction ZVI/Fe 3 O 4 composites prepared by manually grinding a dry mixture of ZVI and magnetite powders using a mortar and pestle (mechanical alloying).…”
Section: Laboratory-synthesized Zvi or Zvi-based Materialsmentioning
confidence: 99%
“…В якості останньої можуть виступати природні глинисті мінерали, ха-рактерним для яких є здатність до утворення міцних поверхневих комплексів з іонами металів за рахунок значної кількості активних центрів, які можуть зна-ходитись як на базальних, так і на бічних гранях крис-талів [8]. Крім природних мінералів в якості стабілі-заторів нанодисперсного заліза також застосовують алюмосилікати, модифіковані різними органічними речовинами [9,10].…”
Section: Hcrounclassified